Roles of apolipoproteins B and E in the cellular binding of very low density lipoproteins. - Krul, E S (1985)
Apoproteins B and E both interact with cellular low density lipoprotein (LDL) apolipoprotein B and E (apo B,E)-receptors, and very low density lipoproteins (VLDL) contain both apo B and apo E. Our aim was to study the relative importance of apo B and apo E in the binding of VLDL subfractions to cells. Two monoclonal anti-LDL-apo B antibodies (464B1B3 and 464B1B6, 2a and 2b, respectively) and two anti-apo E antibodies (1506 A1.4 and 1907 F6.4) were used to inhibit lipoprotein-cell interactions. In confirmation of previous findings, the binding and degradation of 125I-LDL by human fibroblasts were inhibited approximately 90% by antibodies 2a or 2b or the antigen-binding fragments of 2a, whereas the cellular processing of 125I-VLDL3 (Sf20-60), 125I-VLDL2 (Sf60-120), and 125I-VLDL1 (Sf greater than 120) were inhibited by only approximately 50%, approximately 25%, and less than 10%, respectively. The VLDL1-3 and LDL-dependent intracellular esterification of cholesterol with [3H]oleate were inhibited to a similar extent. Other monoclonal anti-human apo B antibodies inhibited lipoprotein-cell interactions much less effectively and nonimmune IgG isolated from mouse serum did not inhibit at all. 20-fold excesses of LDL produced about the same patterns of inhibition of degradation of 125I-VLDL1-3 and LDL by cells as did antibodies 2a and 2b, whereas homologous unlabeled VLDL1-3 in like amounts inhibited the matched 125I-VLDL subfraction more effectively. Two anti-apo E monoclonal antibodies and a polyclonal anti-apo E antibody inhibited cell-mediated degradation of and lipoprotein-dependent cholesterol esterification by VLDL1 but not VLDL3 or LDL. The results suggest that receptor recognition sites on apo E in preference to sites on apo B mediate the cellular binding of hypertriglyceridemic VLDL1. However, the proportion of particles bound via apo B seems to increase as VLDL decreases in size toward LDL, and virtually all of LDL binding is mediated by apo B.